Synthesis of Asymmetric Monomethine Cyanine Dyes with Red‐Shifted Optical Properties. (19th May 2014) - Soriano, Eduardo; Outler, Loretta; Owens, Eric A.; Henary, Maged
<x xml:space="preserve">Abstract</x> Six novel asymmetrical monomethine cyanine dyes were synthesized via the condensation reaction of 1‐butyl‐2‐(methylthio)benzo[c, d]indol‐1‐ium iodide and various 1, 5‐substituted indolenine salts under basic conditions. The dyes were characterized using UV–vis spectroscopy, fluorescence, 1H NMR, 13C NMR, and mass spectrometry; furthermore, the purity of these compounds was observed using LC/ELSD/MS.